SUMBER DAN RISIKO PRODUKSI BUNGA MELATI PUTIH DI DESA DEPOK KECAMATAN KANDEMAN KABUPATEN BATANG - Seruni Sekar Gandhis; Damara Dinda Nirmalasari Zebua (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
Depok Village, Kandeman District, Batang Regency, is one of the centers for white jasmine flower production. White jasmine flower productivity is inseparable from production risk. The purpose of this study was to identify the source of risk and determine the magnitude of the risk of white jasmine flower production. The research method used is qualitative, with 1 key informant and 3 participants for the first purpose, and quantitative, with 17 samples using the standard deviation calculation method and the coefficient of variation. The results sources of production risk are pests and diseases, labor, and weather. The risk of white jasmine flower production has a standard deviation of 138.255 and is still profitable because the CV value is 49% or CV <0.5 and L 2.93 or L> 0. Future research can analyze the impact of risks and production risk management strategies of jasmine flower white.